Psychometric evaluation of the Chinese version of the Academic Resilience Scale-30 (C-ARS-30) in college students - Tan, Wen-ying; Chen, Jia-ni; Lu, Sui-hua; Liu, Chun-qin; Luo, Qing; Ma, Yu; Zhou, Ying; Wong, Thomas K. S.; Chen, Hui-fang; Song, Li-qin; Miao, Chu-yuan; Chen, Jing-wen; et al. (Frontiers in Psychology, 2024)
Background: Amidst the expansion of student enrollment in higher education, the well-being and retention rates of students have emerged as important concerns. Resilience, especially academic resilience, a multidimensional construct that can lead to academic success in adversity, is pivotal in enabling students to successfully cope with academic challenges. While the Academic Resilience Scale-30 (ARS-30) has been validated as an effective instrument in various languages, its applicability for Chinese students in higher education remains unexplored.Objective: This study aims to translate and validate the ARS-30 in Chinese, assessing its reliability and validity among Chinese college students in higher education. Methods: A convenience sample of 1542 students participated in this study. The inventory included the demographic form, Chinese version of ARS-30 (C-ARS-30), 10-item Connor Davidson Resilience Scale (CD-RISC-10), and General Self-Efficacy Scale (GSES). The assessment of validity was conducted by analyzing content validity, construct validity, convergent and discriminant validity, as well as criterion-related validity. Construct validity was evaluated through Confirmatory Factor Analysis (CFA), Exploratory Factor Analysis (EFA) and Exploratory Structural Equation Modeling (ESEM). Reliability analysis was performed using Cronbach's alpha and test-retest reliability. Results: The C-ARS-30 demonstrated commendable content validity, with the CVI value of items ranging from 0.833 to 1.000, and a total scale CVI of 0.986. ESEM analysis revealed a solid four-factor structure, maintaining the scale's 30 items with excellent fit indices (χ²/df = 2.647, CFI = 0.937, TLI = 0.915, RMSEA = 0.057, SRMR = 0.027). The total score of C-ARS-30 exhibited positive correlations with the CD-RISC-10 (r=0.542) and the GSES (r=0.488). The scale demonstrated high internal consistency (Cronbach's α=0.930) and test-retest reliability (0.794, P<0.01).The C-ARS-30 is a reliable and valid instrument for assessing academic resilience among Chinese college students, offering a valuable tool for educational and psychological evaluations.